Lessons from the ionised and molecular mass of post-CE PNe. Issue Volume 16:Issue S366(2020) (November 2020) - Santander-García, Miguel; Jones, David; Alcolea, Javier; Bujarrabal, Valentín; Wesson, Roger
Abstract: Close binary evolution is widely invoked to explain the formation of axisymmetric planetary nebulae, after a brief common envelope phase. The evolution of the primary would be interrupted abruptly, its still quite massive envelope being fully ejected to form the PN, which should be more massive than a planetary nebula coming from the same star, were it single. We test this hypothesis by investigating the ionised and molecular masses of a sample consisting of 21 post-common-envelope planetary nebulae, roughly one fifth of their known total population, and comparing them to a large sample of regular planetary nebulae (not known to host close-binaries). We find that post-common-envelope planetary nebulae arising from single-degenerate systems are, on average, neither more nor less massive than regular planetary nebulae, whereas post-common-envelope planetary nebulae arising from double-degenerate systems are considerably more massive, and show substantially larger linear momenta and kinetic energy than the rest. Reconstruction of the common envelope of four objects further suggests that the mass of single-degenerate nebulae actually amounts to a very small fraction of the envelope of their progenitor stars. This leads to the uncomfortable question of where the rest of the envelope is, raising serious doubts on our understanding of these intriguing objects.